Technologies for learning? An actor-network theory critique of ‘affordances' in research on mobile learning - Gale Parchoma; Steve Wright (Association for Learning Technology, 2011)
How is the link between learner and technology made in mobile learning? Whatis the value of the concept of ‘affordances'? And how does research articulatingthis concept act to position mobile devices as ‘technologies for learning'? Thisliterature review used both unstructured and structured search samples of publishedresearch on mobile learning to critically evaluate the prevalence and influenceof the concept of the affordances of mobile technologies. Actor-networktheory is drawn on as a theoretical lens through which to critically considerhow this concept is articulated, and in particular to explore the way it positionsand controls mobile devices as technologies for learning. Parallels in contemporaryaccounts of mobile learning are drawn with classifications of previous discoursesaround the introduction of computers into schools. An alternativeagenda for mobile learning research is suggested with a focus on authentic andinformal contexts rather than controlled experiments.